CONTRIBUTION OF INFLAMMATION PROCESS (hsCRP LEVELS) IN MIGRAINE DURING ICTAL PHASE - Audry Devisanty Wuysang (Faculty of Medicine, Hasanuddin University., 2016)
ABSTRACTIntroduction: C-reactive protein (CRP), an acute phase protein and a marker of inflammation,has been associated with the risk of cardiovascular disease. CRP has also been suggested tobe abnormal among migraineurs, possibly due to repeated vascular inflammation. Methods:This case-control study was conducted in Wahidin Sudirohusodo General Hospital, Makassar,Indonesia, from June 2013 to January 2014. The aim of this study is to investigate the role ofinflammation in the pathophysiology of an ictal and interictal period of migraine. A t otal of 82patients participated in this study [16 males (19.5%) and 66 females (80.5%)]. The age of ictalperiod patients range between 19-57 years old (median 28, mean 29.54 ± 8.92) and interictalperiod patients range between 20-48 years (median 26, 28,90 ± 7,91). Results: This studyshowed mean hs-CRP level was significantly higher in the ictal period compared to interictalperiod of migraine (6.64 vs 1.87 mg/L). hs-CRP >3mg/L (high risk of cardiovascular event) wasmore common in ictal (78.3%) compared to interictal patients (21,7%), while hs-CRP <1mg/L(low risk of cardiovascular event) was more common in interictal (64.9%) compared to ictalperiod patients (35.1%) (OR=6.646). The contribution of hs-CRP to the ictal period of a migrainewas 17.2%. Conclusion: This study reinforces the view that inflammation processplays some roles in the pathophysiology of a migraine, especially in the ictal period.Keywords: hs-CRP, migraine, ictal.